Possession and Applicability of Signature Character Strengths: What Is Essential for Well-Being, Work Engagement, and Burnout? - Huber, Alexandra (Appl Res Qual Life, 2019)
Signature character strengths can foster health-related outcomes in work and private life, thus being particularly important for endangered occupational groups like physicians. However, situational circumstances need to allow character strengths demonstration (applicability) first to enable their application. Therefore, this study addresses the role of (1) applicability of signature character strengths in work and private life beyond their possession and (2) relationships with well-being, work engagement, and burnout dimensions (emotional exhaustion, depersonalization, and reduced personal accomplishment). Hospital physicians (N = 274) completed an online survey examining their signature character strengths and applicability, well-being, work engagement, and burnout dimensions. The top-five individual signature character strengths were fairness, honesty, judgment, kindness, and love. Hierarchical multiple linear regressions revealed that the possession as well as the applicability of signature character strengths was important in work and private life, but to different degrees. Possessing fairness, honesty, or kindness indicated significant positive relations with subjective well-being, whereas judgment and kindness seemed to negatively interact with reduced personal accomplishment. Hospital physicians’ applicability of fairness, honesty, judgment, and love was particularly essential for their psychological well-being and work engagement, whereas the applicability of fairness (reduced personal accomplishment) and judgment (emotional exhaustion, depersonalization) at work interacted negatively with the respective outcomes. Therefore, creating awareness for individual signature character strengths as well as providing applicability in hospitals and private life could be a promising approach to improve physicians’ well-being and consequently patient care as well as the performance of the health-care system in general.